Factors influencing employee motivation in the Malaysian banking industry - Pereira, Dalina Alpons; Abdullah, Meor Rashydan; Wider, Walton; Tanucan, Jem Cloyd M.; Lee, Harvey Pak Ting; Jiang, Leilei; Udang, Lester Naces (EnPress Publisher, 2024)
Organizations are gradually focusing on creating a healthy workplace for their employees and becoming more people-centric. This occurs because a healthy workforce increases the work performance of the organisation and the personal development of its employees. This study aims to investigate the HR functions that impact employee motivation in the Malaysian banking sector. The three HR functions that were selected were training and development, rewards and recognition, and career management. The study utilised a cross-sectional design, and the research instruments were adapted from a number of past studies. A total of 350 respondents from the Malaysian banking industry were recruited. Using SPSS Version 26.0, the research hypotheses were examined. The results show that rewards and recognition are not significant predictors of employee motivation in the Malaysian banking industry; however, training and development and career management are significant predictors of employee motivation. These results will help the human resources department develop and improve its HR operations.